The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5935/abc.20160137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrate Intake on Myocardial Ischemia-Reperfusion Injury in Diabetic Rats

Abstract: BackgroundCoronary artery disease is 2-3 times more common in diabetic individuals. Dietary nitrate/nitrite has beneficial effects in both diabetes and cardiovascular disease. It also has protective effects against myocardial ischemia-reperfusion (IR) injury in healthy animals. However, the effects of nitrate on myocardial IR injury in diabetic rats have not yet been investigated.ObjectiveWe examined the effects of dietary nitrate on myocardial IR injury in streptozotocin-nicotinamide-induced diabetic rats.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 37 publications
(52 reference statements)
3
22
0
Order By: Relevance
“…Alteration of serum NO concentrations in diabetic conditions are controversial. Some studies have demonstrated that serum NO levels decreased in diabetic rats (Meininger et al 2000;Jeddi et al 2016). On the other hand, other studies have shown increased or unchanged NO levels in diabetes (Mancusi et al 1996;Milsom et al 2002;Adela et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alteration of serum NO concentrations in diabetic conditions are controversial. Some studies have demonstrated that serum NO levels decreased in diabetic rats (Meininger et al 2000;Jeddi et al 2016). On the other hand, other studies have shown increased or unchanged NO levels in diabetes (Mancusi et al 1996;Milsom et al 2002;Adela et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study stated that an increased incidence of diabetes among children may be related to high nitrate concentrations in drinking water, however, other studies have shown beneficial effects of nitrate (Benson et al 2010). In addition, chronic intake of a low dose of nitrate (100 mg/l/day) for 2 months protected the diabetic rat heart from ischemia-reperfusion injury by attenuating oxidative stress (Jeddi et al 2016). Cardiac and renal protective effects of vegetables may relate to their high nitrate contents (Lundberg et al 2006;Ohtake et al 2007).…”
mentioning
confidence: 99%
“…The insulin dose was adjusted in accordance with the blood glucose level. Animals in the nitrate groups received sodium nitrate (Merck KGaA, Darmstadt, Germany) added to their drinking water supplemented with 100 mg l −1 sodium nitrate for 2 months (Jeddi, Khalifi, Ghanbari, Bageripour, & Ghasemi, ). The water intake was measured every day.…”
Section: Methodsmentioning
confidence: 99%
“…Germany) added to their drinking water supplemented with 100 mg l −1 sodium nitrate for 2 months (Jeddi, Khalifi, Ghanbari, Bageripour, & Ghasemi, 2016). The water intake was measured every day.…”
Section: New Findingsmentioning
confidence: 99%
“…Despite the fact that NaNO 2 has not been reliable in the past and has the potential to cause many cancers, it has recently been reported that it can prevent myocardial ischemia-reperfusion injury in diabetic rats by regulating eNOS and iNOS expression and inhibiting lipid peroxidation in the heart [50]. It also prevents hypertension and increases endotheliumdependent relaxation and total NO by regulating eNOS activity [51].…”
Section: Nomentioning
confidence: 99%